2018
DOI: 10.1101/467670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription-factor centric genome mining strategy for discovery of diverse unprecedented RiPP gene clusters

Abstract: Ribosomally synthesized and post-translationally modified peptides (RiPPs) are a rapidly emerging group of natural products with diverse biological activity. Most of their biosynthetic mechanisms are well studied and the "genome mining" strategy based on homology has led to the unearthing of many new ribosomal natural products, including lantipeptides, lasso peptides, cyanobactins. These precursor-centric or biosynthetic protein-centric genome mining strategies have encouraged the discovery of RiPPs natural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 52 publications
(86 reference statements)
3
3
0
Order By: Relevance
“…Next, in addition to the genetic surroundings, each identified Rgg-type regulator led us to the discovery of diverse RiPP gene clusters. 43 As expected, most of the identified QS-regulated RiPP gene clusters belonged to the Ras−RiPP family, which has been reported previously. 31,43 These results indicated that multiple Streptococci widely use radical SAM enzymes to synthesize natural products to facilitate specific microbial communication.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Next, in addition to the genetic surroundings, each identified Rgg-type regulator led us to the discovery of diverse RiPP gene clusters. 43 As expected, most of the identified QS-regulated RiPP gene clusters belonged to the Ras−RiPP family, which has been reported previously. 31,43 These results indicated that multiple Streptococci widely use radical SAM enzymes to synthesize natural products to facilitate specific microbial communication.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…43 As expected, most of the identified QS-regulated RiPP gene clusters belonged to the Ras−RiPP family, which has been reported previously. 31,43 These results indicated that multiple Streptococci widely use radical SAM enzymes to synthesize natural products to facilitate specific microbial communication. In addition to the Ras−RiPPs, we turned our attention to other types of RiPPs.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
See 3 more Smart Citations